Literature and sustainability : concept, text and culture - Johns-Putra, Adeline, 1973-; Parham, John; Squire, Louise (Manchester University Press, 2017)
How might literary scholarship engage with the sustainability debate? Aimed at research scholars and advanced students in literary and environmental studies, this collection brings together twelve essays by leading and up-coming scholars on the theme of literature and sustainability. In today's sociopolitical world, sustainability has become a ubiquitous term, yet one potentially driven to near meaninglessness by the extent of its usage. While much has been written on sustainability in various domains, this volume sets out to foreground the contributions literary scholarship might make to notions of sustainability, both as an idea with a particular history and as an attempt to reconceptualise the way we live. Essays in this volume take a range of approaches, using the tools of literary analysis to interrogate sustainability's various paradoxes and to examine how literature in its various forms might envisage notions of sustainability.